2015
DOI: 10.1111/jace.13791
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformation of Metastable ZnSnO3 Upon Thermal Decomposition by In‐Situ Temperature‐Dependent Raman Spectroscopy

Abstract: Temperature-dependent in-situ Raman spectroscopy is used to investigate the phase transformation of zinc metastannate (ZnSnO 3 ) to zinc orthostannate (Zn 2 SnO 4 ) induced upon annealing in the ambient. ZnSnO 3 microcubes (MCs) were synthesized at room temperature using a simple aqueous synthesis process, followed by characterization using electron microscopy, X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and thermogravimetric analysis (TGA). Annealing of the ZnSnO 3 MCs was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…According to the authors the ZnSnO 3 synthesis at low-temperature (<700 °C) is unfavorable, leading to a mixture of phases, mainly due to its positive formation enthalpies. This decomposition has also been reported to occur at temperature above 500 °C [13,67]. Taking into account the temperature used in this study (200 °C), our results are in fair agreement with this, since with decreasing volume, and consequently pressure, the trend is to achieve higher mixture of phases while the more homogeneous ZnSnO 3 nanowires are obtained when using the higher solution volume, 15 mL.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…According to the authors the ZnSnO 3 synthesis at low-temperature (<700 °C) is unfavorable, leading to a mixture of phases, mainly due to its positive formation enthalpies. This decomposition has also been reported to occur at temperature above 500 °C [13,67]. Taking into account the temperature used in this study (200 °C), our results are in fair agreement with this, since with decreasing volume, and consequently pressure, the trend is to achieve higher mixture of phases while the more homogeneous ZnSnO 3 nanowires are obtained when using the higher solution volume, 15 mL.…”
Section: Resultssupporting
confidence: 90%
“…Gou et al presented these values for the different possible structures of ZnSnO 3 [61]. On the other hand, it is already well-known that the ZnSnO 3 phase is metastable [12,13] and according, for example, to the study reported by Bora et al this phase suffers a decomposition into the thermodynamically stable phases Zn 2 SnO 4 and SnO 2 at temperatures higher than 500 °C [67]. This decomposition can be represented by the following equation:2ZnSnO 3 → Zn 2 SnO 4 + SnO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The broad structure at 650 cm −1 is inconsistent with either and therefore a unique mode of a-ZTO involving both Sn and Zn atoms. Indeed similarities are seen with Raman spectra of a Zn 2 SnO 4 spinel phase seen in high-temperature annealing [52].…”
supporting
confidence: 64%
“…ZnSnO 3 , including a polar LiNbO 3 (LN)‐type (space group: R 3 c , No. 161) and a perovskite‐type structure, is a metastable phase, which can partially decomposed into SnO 2 and Zn 2 SnO 4 above 750°C in atmosphere ambient . Son et al reported that ZnSnO 3 thin film could heteroepitaxially grow on SrTiO 3 (111) substrate and show a high ferroelectric polarization.…”
Section: Introductionmentioning
confidence: 94%
“…161) and a perovskite-type structure, is a metastable phase, which can partially decomposed into SnO 2 and Zn 2 SnO 4 above 750°C in atmosphere ambient. 10,11 Son et al 12 reported that ZnSnO 3 thin film could heteroepitaxially grow on SrTiO 3 (111) substrate and show a high ferroelectric polarization. Zn 2 SnO 4 has an inverse spinel structure with a space group of Fdm.…”
Section: Introductionmentioning
confidence: 99%